The role of narratives in promoting vaccine confidence among Indigenous peoples in Canada, the United States, Australia, and New Zealand: a scoping review - Robert Martell; Maurianne Reade; Lisa Boesch; Davinder P. Kaur; Sandeep Kumar; Michael McArthur; Marion A. Maar (International Journal for Equity in Health)
Abstract Background Many Indigenous youth and young adults in Canada, the United States, Australia, and New Zealand have reported low vaccine confidence, which has been linked to lower vaccination rates for COVID-19, MMR, HPV, DTaP-IPV-Hib, and pneumococcal conjugate vaccines. Narrative-based health promotion approaches, including those focused on strengthening vaccine confidence, have been used in public health interventions. Scoping reviews have become increasingly valued for their rigorous and reproducible exploration of evidence in public health research. The aim of this scoping review was to understand the extent and types of evidence related to the facilitators, challenges, and benefits of narrative-based health promotion approaches in vaccine confidence interventions within Indigenous populations. Methods This review adhered to the Joanna Briggs Institute (JBI) guidelines for scoping reviews using Covidence online software to streamline the review process. Database searches were conducted in MEDLINE, Embase, Web of Science, PsycINFO, and PubMed, as well as Google search to identify both academic and gray literature articles on the role of narratives in promoting vaccine confidence published between January 2000 and April 2024. Charted data were ranked in a numerical summary and analyzed using qualitative content analysis. The review process embraced a two-eyed seeing approach. Results The searches identified 306 records. After the screening process, 45 sources (35 peer-reviewed articles, eight gray literature, and two preprint articles) were included in the final review. The key facilitators of narrative-based approaches to promote vaccine confidence were community engagement, tailored and culturally safe interventions, and trusted messengers and sources of information. The challenges discussed in the literature were linked to mistrust of government and healthcare services and to misinformation narratives. The most frequently reported benefits were the development of community-based resources, culturally safe and relevant interventions, building trust and respectful relationships, and improved vaccination rates. Conclusion This review confirmed the important contribution of narrative-based health promotion approaches in strengthening vaccine confidence among Indigenous populations. This finding underscores the importance of respecting Indigenous sovereignty and engaging community perspectives to repair trust and improve vaccination rates.